2022
DOI: 10.1108/ijchm-11-2021-1373
|View full text |Cite
|
Sign up to set email alerts
|

Linking organizational exploitation to extra-role behaviors: a conservation of resources perspective

Abstract: Purpose Drawing on conservation of resources (COR) theory, this study aims to explore how perceived organizational exploitation affects hospitality employees’ extra-role customer service behaviors by investigating the mediating role of depressed mood at work and the moderating role of reappraisal. Design/methodology/approach This study tested all of the hypotheses using multilevel path analyses with a sample of 340 supervisor–subordinate dyads. Findings The results show that perceived organizational exploi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 50 publications
0
13
0
Order By: Relevance
“…When situations have the potential to be viewed as unfair, detailed explanations can increase employees’ sense of interactional justice, which has been found to decrease unfavorable reactions (Cropanzano et al , 2001). Related work on organizational exploitation has demonstrated that strengthening employee reappraisal skills may ameliorate the negative effects of perceived exploitation on employee mood and extra-role customer service (Cheng et al , 2022) – reappraisal skills may also be important for shaping employee reactions to illegitimate tasks. Finally, supervisors would be well-served to participate in the execution of potentially unreasonable tasks themselves, to model the importance of completing necessary, but potentially illegitimate, tasks (Semmer et al , 2006).…”
Section: Discussionmentioning
confidence: 99%
“…When situations have the potential to be viewed as unfair, detailed explanations can increase employees’ sense of interactional justice, which has been found to decrease unfavorable reactions (Cropanzano et al , 2001). Related work on organizational exploitation has demonstrated that strengthening employee reappraisal skills may ameliorate the negative effects of perceived exploitation on employee mood and extra-role customer service (Cheng et al , 2022) – reappraisal skills may also be important for shaping employee reactions to illegitimate tasks. Finally, supervisors would be well-served to participate in the execution of potentially unreasonable tasks themselves, to model the importance of completing necessary, but potentially illegitimate, tasks (Semmer et al , 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, justice sensitivity strengthens the direct relationship between POE and perceived justice, as well as the indirect effects of POE on workplace deviance. Second, drawing on emotion-centered theory, previous research has investigated various emotions as meditators in the relationships of POE and employees' outcomes (Livne-Ofer et al, 2019;Cheng et al, 2022). However, emotional mechanisms alone cannot fully explain how POE induces employees' coping behaviors.…”
Section: Discussionmentioning
confidence: 99%
“…POE occurs when employees feel that they have been purposefully exploited by their organizations for the benefit of organizations (Cheng et al , 2022; Livne-Ofer et al , 2019). According to Livne-Ofer et al (2019), POE has three elements: POE is defined as a subjective assessment.…”
Section: Theory and Hypothesis Developmentmentioning
confidence: 99%
See 2 more Smart Citations